2017
DOI: 10.1002/bies.201700122
|View full text |Cite
|
Sign up to set email alerts
|

Physical Limits on the Precision of Mitotic Spindle Positioning by Microtubule Pushing forces

Abstract: Summary Tissues are shaped and patterned by mechanical and chemical processes. A key mechanical process is the positioning of the mitotic spindle, which determines the size and location of the daughter cells within the tissue. Recent force and fluctuation measurements indicate that pushing forces, mediated by the polymerization of astral microtubules against the cell cortex, maintain the mitotic spindle at the cell center in C. elegans embryos. The magnitude of the centering forces suggests that the physical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 106 publications
(225 reference statements)
0
52
0
Order By: Relevance
“…In support of pushing, a more recent reevaluation of large asters has indicated that they also contain branched microtubules (Ishihara et al, 2014), thus suggesting that a pushing-based mechanisms could potentially operate. Moreover, it has been argued that even in large cells (circa 50µm) microtubule pushing forces can center centrosomes, and indeed that the pushing force per individual polymerizing microtubule (5-10pN) is equivalent to dyneinbased (1-7pN) pulling forces (Howard and Garzon-Coral, 2017). Thus, in Leech zygotes the cytoplasmic pulling-based mechanism for mitotic spindle centering may not operate, since the whole mitotic apparatus moves in the direction of the shortest microtubules, i.e.…”
Section: Ucd In Zygotes Of Spiralians (Cortical Contraction or Asymmementioning
confidence: 99%
“…In support of pushing, a more recent reevaluation of large asters has indicated that they also contain branched microtubules (Ishihara et al, 2014), thus suggesting that a pushing-based mechanisms could potentially operate. Moreover, it has been argued that even in large cells (circa 50µm) microtubule pushing forces can center centrosomes, and indeed that the pushing force per individual polymerizing microtubule (5-10pN) is equivalent to dyneinbased (1-7pN) pulling forces (Howard and Garzon-Coral, 2017). Thus, in Leech zygotes the cytoplasmic pulling-based mechanism for mitotic spindle centering may not operate, since the whole mitotic apparatus moves in the direction of the shortest microtubules, i.e.…”
Section: Ucd In Zygotes Of Spiralians (Cortical Contraction or Asymmementioning
confidence: 99%
“…Cortical dynein generates pulling forces along these astral microtubules to promote spindle motion (reviewed by Kotak and Gönczy, 2013;McNally, 2013). Pushing forces of astral microtubules against the cortex have also been recently proposed to be involved in spindle positioning in Caenorhabditis elegans embryos (Howard and Garzon-Coral, 2017;Pecreaux et al, 2016). However, the oocytes of most organisms eliminate centrioles during their growth phase, and thus, meiotic spindles lack canonical centrosomes and only have a few or no astral microtubules (Sathananthan et al, 2006;Schuh and Ellenberg, 2007;Szollosi et al, 1972).…”
Section: Spindle Migration During Meiosis Imentioning
confidence: 99%
“…Large-scale reorganization of the microtubule (MT) cytoskeleton is essential for a variety of processes, such as cell division, differentiation and polarization. In dividing cells, a balance of dynein-dependent pulling forces and MT pushing forces determines the positioning of the MTbased mitotic spindle (Howard and Garzon-Coral, 2017;Kotak and Gonczy, 2013). In interphase cells with dense, non-centrosomal MT arrays, such as epithelial or neuronal cells, polarization is a slow process that requires hours, if not days (reviewed in (Kapitein and Hoogenraad, 2015;Meiring et al, 2020)).…”
Section: Introductionmentioning
confidence: 99%